2020
DOI: 10.1136/bmjgast-2020-000406
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening onset of coeliac disease: a case report and literature review

Abstract: BackgroundCoeliac disease (CD) results from an immune-mediated reaction to gluten in genetically predisposed individuals. In rare cases CD may occur with acute features deferring the diagnosis and exposing these patients to possible life-threatening complications. Herein we present the case of a young woman with a coeliac crisis, that is, a sudden clinical onset characterised by severe electrolyte imbalance due to an unknown (previously unrecognised) CD.MethodsThis is a case report and literature review reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Since the enterocyte loss is not sufficiently compensated by a rapid stem cell-derived epithelial replacement, crypt hyperplasia and villous atrophy occur. Moreover, when gliadin peptides get across the altered epithelial lining and reach the bloodstream, they enhance inflammation, thus spreading the immune response and causing extraintestinal manifestations [ 26 , 27 ]. The ubiquitous distribution of TG2, recognized as the main CD autoantigen, along with the increased intestinal permeability (i.e., leaky gut) makes CD a unique immunological systemic disorder favoring the onset of an autoimmune response also in other tissues and organs [ 6 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Celiac Diseasementioning
confidence: 99%
“…Since the enterocyte loss is not sufficiently compensated by a rapid stem cell-derived epithelial replacement, crypt hyperplasia and villous atrophy occur. Moreover, when gliadin peptides get across the altered epithelial lining and reach the bloodstream, they enhance inflammation, thus spreading the immune response and causing extraintestinal manifestations [ 26 , 27 ]. The ubiquitous distribution of TG2, recognized as the main CD autoantigen, along with the increased intestinal permeability (i.e., leaky gut) makes CD a unique immunological systemic disorder favoring the onset of an autoimmune response also in other tissues and organs [ 6 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Celiac Diseasementioning
confidence: 99%
“…This would imply that even a typically chronic disorder, such as CeD, may have acute onset in a small proportion of patients, which emergency physicians should be aware of. Although rarely encountered in clinical practice, this acute onset of CeD requires hospitalization and immediate treatment (i.e., electrolyte replacement and protein correction) to avoid life-threatening complications [ 179 ].…”
Section: Consequences Of Nutrient Malabsorptionmentioning
confidence: 99%
“…To date, the unique treatment that has proven to be effective in CD patients is strictly life-long adherence to the gluten-free diet (GFD), i.e., a diet containing less than 10 mg per day of gluten [1,2]. Lack of adherence to the GFD leads to a significant risk of adverse health consequences [5] and increases mortality from malignancies (e.g., small bowel adenocarcinoma, cancer of the esophagus, B-cell and T-cell non-Hodgkin lymphomas), and in particular intestinal T-cell lymphomas; the risk reduces with strict adherence to the diet [6,7]. Despite rigid compliance to GFD, several studies showed that patients struggle in achieving a full restoring of the gut microbiota; the cause of this phenomenon could be inferred from a persistent genetic influence than to the lack of prebiotics usually ingested with gluten assumption [8].…”
Section: Introductionmentioning
confidence: 99%